Coupling vibration analysis of full-vehicle vehicle-guideway for maglev train. Issue 2 (4th May 2018) - Wang, Keren; Ma, Weihua; Luo, Shihui; Zou, Ruiming; Liang, Xin
ABSTRACT: In order to investigate the effect of inner loop current gain coefficient, time lag and levitation current perturbation on the static suspension stability for the maglev vehicle, a vertical vibration model of HSST-type maglev train with five suspension frames was established. The following conclusions are drawn based on the obtained results: for suppressing vehicle-guideway coupling vibration, the gain coefficient of the inner loop should take a large value in the double loop control, such as a value of 300. If one suspension controller has a large time constant delay, such as a value of 4 ms, and the suspension instability will occur for the vehicle. When the levitation current has a large range perturbation, such as a value of 50%, increasing the control frequency of the levitation controller can suppress the vehicle-guideway coupling vibration of the maglev system to a certain extent.